PREDICTIVE VALUE OF THE GENERAL MOVEMENTS ASSESSMENT IN PRETERM INFANTS: A META-ANALYSIS - Pires, Camila da Silva; Marba, Sérgio Tadeu Martins; Caldas, Jamil Pedro de Siqueira; Stopiglia, Mônica de Carvalho Sanchez (Revista Paulista de Pediatria, 2020)
ABSTRACT Objective: To discuss the predictive value of the General Movements Assessment for the diagnosis of neurodevelopment disorders in preterm newborns. Data source: We conducted a systematic literature review using the following databases: Scientific Electronic Library Online (SciELO), National Library of Medicine, National Institutes of Health (PubMed), and Excerpta Medica Database (EMBASE). The articles were filtered by language, year of publication, population of interest, use of Prechtl’s Method on the Qualitative Assessment of General Movements, and presence of variables related to the predictive value. The Quality Assessment of Diagnostic Accuracy Studies 2 was used to assess the methodology of the included studies. Sensitivity, specificity, Diagnostic Odds Ratio, positive and negative likelihood ratio, and parameter of accuracy were calculated. Data synthesis: Six of 342 articles were included. The evaluation of Writhing Movements is a good indicator for recognizing cerebral palsy, as it has high values for the sensitivity and accuracy parameters. The evaluation of Fidgety Movements has the strongest predictive validity for cerebral palsy, as it has high values in all measures of diagnostic accuracy. The quality assessment shows high risk of bias for patient selection and flow and timing of the evaluation. Therefore, the scale has potential to detect individuals with neurodevelopment disorders. However, the studies presented limitations regarding the selection of subjects and the assessment of neurological outcomes. Conclusions: Despite the high predictive values of the tool to identify neurological disorders, research on the subject is required due to the heterogeneity of the current studies. RESUMO Objetivo: Analisar o valor preditivo da General Movements Assessment para o diagnóstico de alterações do neurodesenvolvimento em recém-nascidos pré-termo. Fonte de dados: Foi realizada uma revisão sistemática da literatura utilizando as bases de dados: Scientific Electronic Library Online (SciELO), National Library of Medicine, National Institutes of Health (PubMed) e Excerpta Medica Database (EMBASE). Os artigos foram filtrados por idioma, ano de publicação, população de interesse, utilização do Método Prechtl de avaliação e presença das variáveis relacionadas ao valor preditivo da escala. O Quality Assessment of Diagnostic Accuracy Studies 2 foi utilizado para avaliar a metodologia dos artigos. Foi realizado o cálculo de sensibilidade, especificidade, Diagnostic Odds Ratio, razão de verossimilhanças positiva e negativa e parâmetro de acurácia. Síntese dos dados: Foram incluídos seis artigos dentre os 342 encontrados. A escala, quando realizada no período Writhing Movements, possui bom poder discriminativo para o desfecho paralisia cerebral, com valores elevados de sensibilidade e acurácia. Quando realizada no período Fidgety Movements, possui maior valor preditivo para paralisia cerebral, com valores elevados em todas as medidas de acurácia diagnóstica. O risco de viés foi considerado elevado na seleção de pacientes e no fluxo e momento da avaliação. Desse modo, a escala tem potencial para detectar indivíduos que evoluíram com alterações do neurodesenvolvimento, porém, os artigos apresentaram limitações quanto à seleção dos sujeitos e à forma de avaliação do desfecho neurológico. Conclusões: Apesar dos altos valores preditivos descritos para identificação de alterações neurológicas, novas pesquisas são necessárias, devido à heterogeneidade dos estudos e ao método de avaliação a longo prazo do neurodesenvolvimento.